2016
DOI: 10.1136/bmjopen-2016-013183
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in the prevalence of metabolic syndrome and its risk factors in the Suriname Health Study: a cross-sectional population study

Abstract: BackgroundThe metabolic syndrome (MetS) indicates increased risk for cardiovascular disease and type 2 diabetes. We estimated the overall and ethnic-specific prevalence of MetS and explored the associations of risk factors with MetS among Amerindian, Creole, Hindustani, Javanese, Maroon and Mixed ethnic groups.MethodWe used the 2009 Joint Interim Statement (JIS) to define MetS in a subgroup of 2946 participants of the Suriname Health Study, a national survey designed according to the WHO Steps guidelines. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Similarly, from a study in Suriname, South America, MetS prevalence was reported as the highest among the Hindustanis (descendent of Indians), compared to other Suriname races (40). The prevalence values of high blood pressure, low HDL-cholesterol and hyperglycemia were also high among the Suriname Hindustanis (40). In our study, results show that the Chinese appear to be less prone to developing MetS, while the Indians in Johor are at a greater risk of developing MetS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, from a study in Suriname, South America, MetS prevalence was reported as the highest among the Hindustanis (descendent of Indians), compared to other Suriname races (40). The prevalence values of high blood pressure, low HDL-cholesterol and hyperglycemia were also high among the Suriname Hindustanis (40). In our study, results show that the Chinese appear to be less prone to developing MetS, while the Indians in Johor are at a greater risk of developing MetS.…”
Section: Discussionsupporting
confidence: 79%
“…The Cree Indians also had a higher prevalence of central obesity and hyperglycemia compared to other races in the country (14). Similarly, from a study in Suriname, South America, MetS prevalence was reported as the highest among the Hindustanis (descendent of Indians), compared to other Suriname races (40). The prevalence values of high blood pressure, low HDL-cholesterol and hyperglycemia were also high among the Suriname Hindustanis (40).…”
Section: Discussionmentioning
confidence: 83%
“…Acculturation of lifestyle is already increasing among the indigenous in the interior, especially among the Wayana, where an increase in consumption of canned and processed foods has been documented [20,21]. The prevalence of MeTS in both our study subgroups was comparable to the national average for women (42.3%) [12]. Both diabetes mellitus and hypertension were less prevalent than the national average for women (resp.…”
Section: Discussionmentioning
confidence: 45%
“…We focused on women since the Suriname Health study showed that Indigenous women had the second highest MeTS prevalence nationwide [12].…”
mentioning
confidence: 99%
“…Recent studies have shown that the prevalence of obesity, tobacco use and physical inactivity are still relatively low among these populations [36,37]. This should be studied further and is important for the development of prevention policies.…”
Section: Discussionmentioning
confidence: 99%